2023
DOI: 10.1002/cncr.34935
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblasts contribute to the immunosuppressive landscape and influence the efficacy of the combination therapy of PD‐1 inhibitors and antiangiogenic agents in hepatocellular carcinoma

Abstract: BackgroundChronic inflammation is considered the most critical predisposing factor of hepatocellular carcinoma (HCC), with inflammatory cell heterogeneity, hepatic fibrosis accumulation, and abnormal vascular proliferation as prominent features of the HCC tumor microenvironment (TME). Cancer‐associated fibroblasts (CAFs) play a key role in HCC TME remodeling. Therefore, the level of abundance of CAFs may significantly affect the prognosis and outcome in HCC patients.MethodsUnsupervised clustering was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Nurdles from spills are endemic . Collecting all the spilled material is an unrealistic objective, posing the oft question, “How clean is clean?” , Following previous nurdle spills, cleanup efforts predominantly relied on community-based activities to recover spilled material. , After a spill in the North Sea, efforts focused on removing any piece of plastic from beaches . However, this is a false equivalency because different plastics behave differently in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Nurdles from spills are endemic . Collecting all the spilled material is an unrealistic objective, posing the oft question, “How clean is clean?” , Following previous nurdle spills, cleanup efforts predominantly relied on community-based activities to recover spilled material. , After a spill in the North Sea, efforts focused on removing any piece of plastic from beaches . However, this is a false equivalency because different plastics behave differently in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, as demonstrated by Zhao J. et al [152], through the secretion of CXCL12, a chemokine that induces the upregulation of FOLR1 in HCC cells, CAFs contribute to resistance to sorafenib therapy. Concurrently, Chen Q et al have indicated that combination therapy involving PD-1 inhibitors and anti-angiogenic drugs may hold greater promise for patients with elevated CAF abundance compared to single-agent treatment strategies [153].…”
Section: The Role Of Cancer-associated Fibroblasts (Cafs) In the Hcc ...mentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) cell-derived exosomal miRNA-21 directly targeted PTEN (gene of phosphate and tension homology deleted on chromosome ten), leading to the activation of PDK1/AKT signalling in Hepatic stellate cells (HSCs), which are then transformed into CAFs [ 127 ]. Activated CAFs further promote cancer angiogenesis by secreting angiogenic cytokines, including VEGF, MMP2, MMP9, bFGF and TGF-β [ 128 ]. Furthmore, miR-21 can also shape a vascular microenvironment for HCC via the STAT3/VEGF signalling pathway, and miR-221 can activate the SAND/NF-κB pathway to upregulate the expression of CXCL16, which is an angiogenic factor [ 129 ].…”
Section: Introductionmentioning
confidence: 99%